DEVELOPMENT OF AN ELECTRIC ENERGY GENERATOR SLAB PROTOTYPE USING ELECTRICAL SENSORS - Dávila Cadena, Andrea Carolina
Nowadays, Large-scale energy production depends on non-renewable sources of energy, the so-called fossil fuels such as coal, oil and natural gas; developed or developing economies have a dependence on this type of non-renewable raw materials, given this situation, we seek to propose an alternative energy source that can be “green”, clean and sustainable compared to those used in the world. Renewable energies are attractive to electrical systems in countries that have the natural and ideal conditions for incorporation; these are solar radiation, water sources or wind potential. Colombia is a country that has a lot of natural resources, which has allowed it to obtain energy from renewable sources. One of the sources of clean, fully renewable energy is piezoelectricity, which are electrical impulses generated by the deformation of certain mineral crystals. Thus, the main objective of this research is the development of a prototype of a slab generating electricity, based on the piezoelectric principle. The theoretical framework is supported by the postulates of the following authors: (Cortés & Arango Londoño, 2017); (Muriel, 2013); (Medina, Álvarez, & Morales, 2017); (Pérez Pineda & Velázquez Alfaro, 2016).The methodology applied in this research is experimental, descriptive and field type; and will be developed in the following phases: Information Collection, Analysis, Design and Construction of the prototype.